Interpreting the cloud cover - aerosol optical depth relationship found in satellite data using a general circulation model - Quaas, J; Stevens, B; Stier, P; Lohmann, U (2010)
Statistical analysis of satellite data shows a positive correlation between aerosol optical depth (AOD) and total cloud cover (TCC). Reasons for this relationship have been disputed in recent literature. The aim of this study is to explore how different processes contribute to one model's analog of the positive correlation between aerosol optical depth and total cloud cover seen in the satellite retrievals. We compare the slope of the linear regression between the logarithm of TCC and the logarithm of AOD, or the strength of the relationship, as derived from three satellite data sets to the ones simulated by a global aerosol-climate model. We analyse model results from two different simulations with and without a parameterisation of aerosol indirect effects, and using dry compared to humidified AOD. Perhaps not surprisingly we find that no single one of the hypotheses discussed in the literature is able to uniquely explain the positive relationship. However the dominant contribution to the model's AOD-TCC relationship can be attributed to aerosol swelling in regions where humidity is high and clouds are coincidentally found. This finding leads us to hypothesise that much of the AOD-TCC relationship seen in the satellite data is also carried by such a process, rather than the direct effects of the aerosols on the cloud fields themselves. © Author(s) 2010.